Circulation of a novel human respiratory syncytial virus Group B genotype during the 2014–2015 season in Catalonia (Spain). (January 2016) - Gimferrer, L.; Andrés, C.; Campins, M.; Codina, M.G.; Rodrigo, J.A.; Melendo, S.; Martin, M.C.; Fuentes, F.; Saiz, M.R.; Esperalba, J.; Bruguera, A.; Vilca, L.M.; et al.
Abstract: Human respiratory syncytial virus (HRSV) is one of the most common viral aetiological agents in the youngest population. In the present study a novel HRSV-B BA genotype is first described based on the phylogenetic analysis of the coding hypervariable region 2 sequences of G protein from strains detected during the 2014–2015 season. Among all strains detected in the last season, 44% belonged to this new genotype. Therefore, it highlights the importance of a continuous HRSV surveillance to monitor the emergence and spread of new genotypes or variants with genetic changes that may affect antigenic and tropism features.